Realizing Lausanne’s Holistic Mission in the Context of Poverty in Indonesia - Anggreani, Friskilia Putri Diah; Hauw, Andreas (Sekolah Tinggi Teologi SAAT, 2021)
Poverty is a latent and global social problem in Indonesia. The outbreak of the Covid-19 that hit the world and Indonesia in early 2020 resulted in an economic recession in Indonesia. In this social context, the evangelicals in Indonesia have not taken this problem seriously. Despite that ignorance regarding the issue of poverty, there have been significant changes in the Lausanne Movement, which is reflected in three documents from this movement, Lausanne Covenant, Manila Manifesto, and The Cape Town Commitment. Considering this background, the authors use the point of view of the Lausanne Movement to invite the Indonesian evangelicals to see the context of poverty as an essential factor that must be included in their theological commitment. Furthermore, this article is meant to serve as a theological trigger for the evangelicals in Indonesia to reconsider the significance of their role in the public sphere, particularly in addressing the issue of poverty. Finally, the article’s contribution is three theological points that might be proposals for the Evangelicals in Indonesia to carry out God’s holistic mission for social transformation in the society. The authors propose three theological principles based on the three documents of the Lausanne Movement to inspire Evangelicals in Indonesia to carry out God’s mission for the holistic transformation of society; that is, God’s mission is understood in terms of the wholeness of God’s creation, focused on humanity, and made possible only by the redemptive act of Jesus Christ.